Polyneoplasia associated with gastrointestinal stromal tumor: literature review and case report - N. V. Vasilyev; V. A. Markovich; I. G. Frolova; R. V. Ermolenko; A. A. Maltseva; О. I. Kovalev; P. G. Lyutikova (Сибирский онкологический журнал)
The purpose of the study was to demonstrate a rare clinical case of polyneoplasia associated with GIST, combining three malignant neoplasms of different nosological affiliation and different tissue origin. Scientific interest is caused by the need to study polyneoplasia associated with Gist, which can be explained by the concept of Rodriquenz M.G. et al. (2016), suggesting the special role of a solitary GisT in the potential development of polyneoplasia.Material and Methods. The search for relevant sources was carried out in the Medline, Cochrane Library, Elibrary systems, includibg publications from January 2009 to October 2019. Of the 507 studies, 21 were used to write a systematic review.Results. In the vast majority of cases, polyneoplasia is represented by two malignant neoplasms in a single patient. Primary multiple metachronous and primary multiple synchronous tumors with three or more tumors are observed very rarely. Among all multiple primary tumors, our attention was drawn to polyneoplasia containing GisT. A neoplasm associated with a GisT is localized mainly in the gastrointestinal tract, and also occurs in the organs of the urinary system, female genital system, thyroid gland, breast, lungs, and testicles.Conclusion. This clinical case is a rather rare phenomenon of polyneoplasia associated with GisT of rectum, which combines three malignant neoplasms. It should be noted that primary Gist in the rectum occurs in 4% of cases.